TRANSCENDENT PRINCIPLES OF MA‘ĀD IN THE QUR`AN - Hasyim Adnani (Tanzil: Jurnal Studi Al-Quran, 2023)
This article explains the various principles and discourses in understanding ma‘ād, depending on the point of view of the school of thought, whether theological, rationalist or transcendental theosophy (al-ḥikmah al-muta‘āliyah). Each point of view will give rise to different meanings and implications as a result and consequence of that view. Resurrection is not only a matter of ideology but is a discussion studied by philosophers to explore its philosophical values. The verses of the Koran also confirm the existence of the day of resurrection. However, in practice, scholars and intellectuals differ in interpreting the aspect of resurrection referred to in these verses of the Qur'an. Spiritual awakening or physical resurrection is a dialogue that is often discussed in the context of understanding the day of resurrection. Through qualitative research and a philosophical approach, the author tries to juxtapose the principles of transcendental theosophy as an analytical tool for understanding the concept of ma‘ād. Apart from being able to apply the transcendent theosophical principle to understand transcendent ma‘ād, this principle also accommodates the basic principles contained in theological, philosophical, ‘irfān and Sufism thought. So, the results obtained from this research are that the concept of ma‘ād needs to be understood through the principles of Islamic philosophy so that a complete understanding will be created in understanding the concept of ma‘ād. In the context of Islamic philosophy, especially transcendental theosophy (al-ḥikmah al-muta‘āliyah), various theories are very relevant in explaining the concept of ma‘ād, especially in understanding the context of the day of resurrection in the Qur'an.